INVESTIGATING THE CAUSES OF EFL STUDENTS' FOREIGN LANGUAGE ANXIETY AND THEIR SPEAKING PERFORMANCE - Syaima, Hakim (2018)
The current study aimed at investigating the factors that cause students' anxiety in speaking English and finding any correlation between the anxiety and the students' speaking performance. A case study was employed as the research design of this study. The participants of the study were 33 students of Science program class in one senior high school in Bandung. The data were obtained from questionnaires, interviews, and one speaking test. The results showed that self-perception, low proficiency in speaking English, learners' beliefs about language learning, teachers' beliefs about language learning, and classroom procedure were considered as the main factors that caused students to be anxious in speaking English. It is also found that there is a negative correlation between students' speaking anxiety and their speaking performance. The findings indicated that students were anxious in speaking English. The five factors and their anxiety can predict the quality of the students' speaking performance. The higher the students' anxiety, the lower the students' speaking performance.